Risk assessment of arteriovenous fistulas focusing on the relationships between the properties of shunted blood flow sounds and a medical/surgical history of hemodialysis patients. - Keiko Tanaka; Keisuke Nishijima; Ken'ichi Furuya; Satoko Shin; Michiaki Kai (PLoS ONE)
The global prevalence of end-stage kidney failure is increasing, with hemodialysis as the primary treatment. An arteriovenous fistula serves as a critical lifeline for patients undergoing hemodialysis, yet its function often deteriorates due to complications such as narrowing or blockage of the blood vessels. This study aimed to clarify the relationships between the sound properties of blood flow through arteriovenous fistulas and a medical/surgical history of patients undergoing hemodialysis by analyzing the distribution of sound frequencies from 100 to 4,000 Hz. Data were collected from 53 patients to identify two key parameters: the time point within one cycle of arteriovenous fistula sounds where the power distribution reached its peak, expressed as a percentage, and the specific frequency where the power was highest within the analyzed range. The results showed that well-functioning arteriovenous fistulas exhibited peak power within the first 25 percent of the sound cycle and the highest power at 200 Hz. In contrast, higher peak percentages and lower power at 200 Hz were associated with surgical interventions due to complications such as narrowing or blockage of the arteriovenous fistula. These findings suggest that the sound properties of arteriovenous fistulas, combined with patient-specific characteristics, may serve as non-invasive indicators of arteriovenous fistula function and help predict the risk of complications. This approach provides valuable insights for improving the management of arteriovenous fistulas and patient outcomes in hemodialysis therapy.